In Situ Generation of Artificial Solid‐Electrolyte Interphases on 3D Conducting Scaffolds for High‐Performance Lithium‐Metal Anodes. Issue 8 (29th January 2020) - Zhai, Pengbo; Wei, Yi; Xiao, Jing; Liu, Wei; Zuo, Jinghan; Gu, Xiaokang; Yang, Weiwei; Cui, Shiqiang; Li, Bin; Yang, Shubin; Gong, Yongji
Abstract: Rational structure design of the current collector along with further engineering of the solid‐electrolyte interphases (SEI) layer is one of the most promising strategies to achieve uniform Li deposition and inhibit uncontrolled growth of Li dendrites. Here, a Li2 S layer as an artificial SEI with high compositional uniformity and high lithium ion conductivity is in situ generated on the surface of the 3D porous Cu current collector to regulate homogeneous Li plating/stripping. Both simulations and experiments demonstrate that the Li2 S protective layer can passivate the porous Cu skeleton and balance the transport rate of lithium ions and electrons, thereby alleviating the agglomerated Li deposition at the top of the electrode or at the defect area of the SEI layer. As a result, the modified current collector exhibits long‐term cycling of 500 cycles at 1 mA cm −2 and stable electrodeposition capabilities of 4 mAh cm −2 at an ultrahigh current density of 4 mA cm −2 . Furthermore, full batteries (LiFePO4 as cathode) paired with this designed 3D anode with only ≈200% extra lithium show superior stability and rate performance than the batteries paired with lithium foil (≈3000% extra lithium). These explorations provide new strategies for developing high‐performance Li metal anodes. Abstract : An artificial Li2 S layer with high compositional uniformity and high lithium ion conductivity is in situ generated on the surface of a 3D Cu nanowire–Cu foam current collector. Synergistic modulation of local current density, solid‐electrolyte interphase (SEI) breakage and the ratio of electron/ion conductivity achieved on the designed structure guides uniform Li deposition, improving the Li utilization and cycling stability of the anode.